2019
DOI: 10.1021/acsami.9b07294
|View full text |Cite
|
Sign up to set email alerts
|

Promising Ti3C2Tx MXene/Ni Chain Hybrid with Excellent Electromagnetic Wave Absorption and Shielding Capacity

Abstract: Electromagnetic (EM) pollution affecting people's normal lives and health has attracted considerable attention in the current society. In this work, a promising EM wave absorption and shielding material, MXene/Ni hybrid, composed of one-dimensional Ni nanochains and two-dimensional Ti 3 C 2 T x nanosheets (MXene), is successfully designed and developed. As expected, excellent EM wave absorption and shielding properties are obtained and controlled by only adjusting the MXene content in the hybrid. A minimum ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
152
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 390 publications
(154 citation statements)
references
References 62 publications
2
152
0
Order By: Relevance
“…Ti 3 C 2 T x MXene was synthesized by etching Al atom layer from the Ti 3 AlC 2 phase according to the previous work. [ 38–40 ] Briefly, 2 g of LiF was put into 40 mL of 9 m HCl in a polytetrafluoroethylene (PTFE) container. After 30 min stirring, 2 g of Ti 3 AlC 2 powder (<38 µm) was slowly added to the container, and kept for 24 h at 35 °C.…”
Section: Methodsmentioning
confidence: 99%
“…Ti 3 C 2 T x MXene was synthesized by etching Al atom layer from the Ti 3 AlC 2 phase according to the previous work. [ 38–40 ] Briefly, 2 g of LiF was put into 40 mL of 9 m HCl in a polytetrafluoroethylene (PTFE) container. After 30 min stirring, 2 g of Ti 3 AlC 2 powder (<38 µm) was slowly added to the container, and kept for 24 h at 35 °C.…”
Section: Methodsmentioning
confidence: 99%
“…The Ti 2p-related four peaks for CM at 455.8, 459.6, 461.5, and 465.2 eV correspond to CTiT x 2p 3/2 , TiO 2p 3/2 , CTiT x 2p 1/2 , and TiO 2p 1/2 bonds, respectively ( Figure 4d). [7,40] The C 1s-related four peaks located at 282.0, 285.0, 286.4, and 289.2 eV correspond to CTiT x , CC/ CC, CO and OCO bonds, respectively (Figure 4e). [39] Combining the O 1s-related and F 1s-related spectra ( Figure S4a,b, Supporting Information), it can be deduced that there are abundant OH, O, and F groups on the surface of Ti 3 C 2 T x .…”
Section: Fabrication Of Cf@mxene@mosmentioning
confidence: 99%
“…Generally, the design and fabrication of microwave absorption (MA) materials mainly focus on two aspects: the selection of proper elements and the construction of specific structures. According to the existing cognition, 1D MA‐related materials, benefiting from the anisotropy and high aspect ratio, are prone to form carrier transport path in the axial direction under EM fields, which consumes the energy of EM wave through conducting loss; [ 5–7 ] 2D MA‐related materials promote the attenuation of EM wave mainly depending on the polarization enhancement caused by the high specific surface area and the multiple reflections between the layers, [ 8–10 ] while 3D materials improve the impedance matching of materials by introducing pores or gaps to enhance MA properties. [ 11–16 ] In particular, the latest reports have showed that hierarchical 3D structures containing 1D or 2D cells exhibit exciting MA properties.…”
Section: Introductionmentioning
confidence: 99%
“…A minimum reflection coefficient of G/TiC/Ti 3 C 2 with the thickness of 2.1 mm reaches −63 dB and the effective absorption bandwidth is more than 3.5 GHz. Liu's team successful designed MXene/Ni hybrid applied for electromagnetic wave absorption and shielding as shown in Figure b . A minimum reflection loss of −49.9 dB is achieved with a thickness of 1.75 mm at 11.9 GHz.…”
Section: Electrochemical Energy Conversion and Storage Applicationsmentioning
confidence: 99%